The Efficacy of Mentalization-Based Treatment for Children With Internalizing and Externalizing Problems: A Randomized Controlled Trial - Halfon, Sibel; Besiroglu, Burcu; Bulut, Pelinsu; Epozdemir, Sevin; Aydin, Gizem I.; Koc, H. Burak; Midgley, Nick (Elsevier Science Inc, 2025)
Objective: High comorbidity in childhood emotional and behavioral disorders calls for transdiagnostic interventions that can address both internalizing and externalizing problems. Mentalization-Based Treatment for Children (MBT-C) is a transdiagnostic, time-limited individual child psychotherapy with parallel parent sessions that aims to promote mentalization and emotion regulation. This pragmatic randomized controlled superiority trial investigated the efficacy of MBT-C compared with a group-based parenting and child social skills intervention (PSSG) at 12 weeks (primary end point) and 36-week follow-up (secondary end point). Method: The trial included 222 children (mean age-7.89; 34% girls) at clinical levels of internalizing, externalizing, or co-occurring internalizing and externalizing problems and their families equally randomized to MBT-C or PSSG. Assessments took place at baseline, 8 and 12 weeks, and 24-and 36-week follow-up. Primary outcomes were children's internalizing, externalizing, and total problems. Secondary outcomes were parent and child emotion regulation, child global function, parent mentalizing, and parenting stress. Results: There were no statistically significant differences between MBT-C and PSSG in reducing children's total, internalizing, or externalizing problems at 12 weeks; however, MBT-C was superior at 36 weeks on total problems with a small effect (d-0.479, 95% CI [0.105, 0.854]). MBT-C was also superior in improving emotion regulation of parents (d-0.248, 95% CI [0.002, 0.493]) and children (d-0.221, 95% CI [ 0.435, 0.006]) and child-reported problems (d-0.331, 95% CI [0.029, 0.633]) at 12 weeks with small effects. These differential treatment effects were maintained during follow-up. Conclusion: MBT-C demonstrated a small superior effect to PSSG in treating overall problems over the longer term, but not immediately after the intervention, in school-age children with internalizing and externalizing problems. However, as a single-site study, generalizability is limited, and further research supporting treatment efficacy is warranted. Plain language summary: This randomized controlled trial compared the efficacy of Mentalization-Based Treatment for Children (MBT-C) to a parenting and child social skills group (PSSG) in 222 school-age children with internalizing and externalizing problems. There were significant improvements in children's emotional and behavioral problems in both interventions at the end of the treatments. However, children who received MBT-C showed significantly more reductions in their levels of problems compared to children who received PSSG at 6-month follow-up. Compared to PSSG, both children and parents in MBT-C showed significantly greater improvements in their emotion regulation capacities at the end of treatment, which were sustained during follow-up. Overall, the effect sizes for these relative improvements at follow-up were small. Clinical trial registration information: The Effectiveness and Change Mechanisms of Mentalization Based Therapy for Children (MBT-C); NCT05290714; https://clinicaltrials.gov/study/NCT05290714.
Keywords: Child Mental Health; Externalizing Problems; Internalizing Problems; Mentalization-Based Treatment For Children; Transdiagnostic Interventions